General and sports nutrition knowledge among Jordanian adult coaches and athletes: A cross-sectional survey. - Nour Amin Elsahoryi; Gina Trakman; Ayah Al Kilani (PLoS ONE, 2021)
Background Nutrition knowledge (NK) is a modifiable determinant of diet intake and can positively influence athletic performance. This study aimed to (1) adapt and translate a validated general and sports NK questionnaire into Arabic (2) assess the NK of Jordanian sportspeople, and (3) evaluate the relationship between NK and various sociodemographic factors. Methods The Abridged Nutrition for Sport Knowledge Questionnaire (ANSKQ) was translated into Arabic using forward-backward translation and underwent pilot testing and psychometric validation (internal consistency, test-retest reliability, inter-rater agreement) using a convenience sample of 30 individuals. Following ANSKQ validation, athletes a from 50 sport institutes in Jordan were invited (via email) to complete the Arabic ANSKQ online. Differences in NK based on demographics were analysed using t-test or ANOVA for continuous variables and chi-square tests for categorical variables. The ability of demographic factors to predict NK score-category (poor/good/average/excellent) was assessed using multivariate logistic regression. Results The Arabic ANSKQ had excellent internal consistency (Cronbach's alpha = 0.92), test-retest reliability (Pearson r = 0.926) and inter-rater agreement (Cohen's k statistic = 0.89). A total of 3636 eligible participants completed the Arabic ANSKQ. Participants were mostly athletes (91.4%), female (68.0%), had normal BMI (50.6%), and played high-intensity sports (59.6%). 88.3% of participants had poor NK (<50%). There were statistically significant differences in NK score based on participant role (athlete vs coach), age, gender, BMI, nationality, smoking, years playing sport, sport frequency, sport intensity, and nutrition training. Multivariate modelling showed participant role, BMI, education level, sport frequency and nutrition training were predictors of NK category. Conclusions In conclusion, Jordanian sportspeople have poor NK and may benefit from increased nutrition training.